The Effect of Platelet-rich Plasma Injections on Improving Motor Function in Runners with Achilles Tendinitis - Mohammed Abdulsalam Fadel Mahdi (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
This study aims to investigate the effect of Platelet-Rich Plasma (PRP) injections on improving motor function in runners with Achilles tendinitis. Achilles tendinitis is considered one of the most common injuries among runners due to the repetitive mechanical stress placed on the tendon during training and competition. The researcher adopted the experimental method with a single-group design as it suits the nature of the study. The sample consisted of eight runners diagnosed with Achilles tendinitis from Baghdad clubs, selected purposively. The participants underwent a PRP injection protocol in accordance with approved medical procedures, and motor function was assessed before and after the injection using the Visual Analogue Scale (VAS), the Single-Leg Hop Test, and the VISA-A questionnaire for Achilles tendon- -function assessment. The results revealed a statistically significant improvement in all motor function indicators following the injection protocol, with reduced pain intensity and improved hopping ability and overall tendon functional performance. The study concluded that PRP injections represent an effective and safe therapeutic option for treating Achilles tendinitis in runners and improving their motor function.